Nisin in Combination with Cinnamaldehyde and EDTA to Control Growth of Escherichia coli Strains of Swine Origin - Des Field; Inès Baghou; Mary C. Rea; Gillian E. Gardiner; R. Paul Ross; Colin Hill (MDPI AG, 2017)
Post-weaning diarrhoea (PWD) due to enterotoxigenic Escherichia coli (ETEC) is an economically important disease in pig production worldwide. Although antibiotics have contributed significantly to mitigate the economic losses caused by PWD, there is major concern over the increased incidence of antimicrobial resistance among bacteria isolated from pigs. Consequently, suitable alternatives that are safe and effective are urgently required. Many naturally occurring compounds, including the antimicrobial peptide nisin and a number of plant essential oils, have been widely studied and are reported to be effective as antimicrobial agents against pathogenic microorganisms. Here, we evaluate the potential of nisin in combination with the essential oil cinnamaldehyde and ethylenediaminetetraacetic acid (EDTA) to control the growth of E. coli strains of swine origin including two characterized as ETEC. The results reveal that the use of nisin (10 μM) with low concentrations of trans-cinnamaldehyde (125 μg/mL) and EDTA (0.25-2%) resulted in extended lag phases of growth compared to when either antimicrobial is used alone. Further analysis through kill curves revealed that an approximate 1-log reduction in E. coli cell counts was observed against the majority of targets tested following 3 h incubation. These results highlight the potential benefits of combining the natural antimicrobial nisin with trans-cinnamaldehyde and EDTA as a new approach for the inhibition of E. coli strains of swine origin.